Scientific Opinion on the evaluation of the pest risk analysis on Pomacea insularum, the island apple snail, prepared by the Spanish Ministry of Environment and Rural and Marine Affairs - EFSA Panel on Plant Health (PLH) (EFSA Journal)
Abstract The Panel considers the Spanish pest risk analysis (PRA) to be clear and to provide appropriate supporting evidence. However, (i) the environmental impact assessment is incomplete and (ii) the estimates for the potentially endangered area are too limited. The Panel points out that large areas of the European Union have climatic conditions, that are very similar to those of the areas of native distribution of Pomacea spp. snails, and suitable host plants are available. The Panel agrees with the Spanish PRA on the following points with regard to the risk assessment area: (i) the potential consequences of the organism for rice crops are major; (ii) the probability for establishment of the organism is very likely and (iii) the probability of spread is estimated as likely. The Panel disagrees with the Spanish PRA on the following points and considers (i) the effects on the environment to be massive under suitable environmental conditions in the PRA area and (ii) the probability of entry of the organism to be high. Regarding risk reduction options the Panel agrees with the Spanish PRA that no single risk reduction method is sufficient to halt the introduction and spread of Pomacea spp. snails in the PRA area. However, a legislative ban on import of Pomacea spp. is the only risk reduction option identified that can reduce the probability of entry. The many other risk reduction options listed will help to reduce the probability of spread within the PRA area. The Panel considers that the risk reduction options should target the canaliculata complex, as Pomacea insularum and P. canaliculata, as well as other species from the complex, are almost indistinguishable. This is of particular importance for risk reduction options addressing both breeding and trade of the organism.